Modal Sosial dalam Pengembangan Ekowisata di Desa Marente Kecamatan Alas Kabupaten Sumbawa - Diana Alfianti; Solikatun Solikatun; Ratih Rahmawati (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2021)
Various Research with title of "Social Capital in Ecotourism Development in Marente Village of Alas Sub-district of Sumbawa District". This research is a qualitative research to discover and identify the forms of the social capital of society and the problems that occurred during the development process and efforts to overcome the problems in the development of ecotourism in Marente village. The research used the social capital theory by Putnam and Woolcocks. The research uses qualitative descriptive methods, data collection techniques using open and profound interview techniques, field observations and documentation results. Data analysis are data reduction, data presentation and conclusions/verifications. The results showed the form of social capital in Marente village community in the development of ecotourism consisting of values and norms, beliefs and networks. Values in the form of the attitude of friendliness, the value of togetherness, religious values and the value of environmental responsibility and norms to regulate the development of ecotourism. Community trust on ecotourism managers and related agencies. Network or cooperation relationship of the community in Marente village with village, district and provincial governments. Generally the obstacles faced in the ecotourism development are related to funds, facilities and infrastructure, technology are less good, lack of competent in human resources, lack of public awareness on tourism and environmental hygiene. Therefore, the effort is to propose funding proposals to related parties, to participate in training on ecotourism development and carried out socialization related to the importance of tourism and environmental hygiene.